IMPLEMENTASI PERATURAN KAPOLRI NOMOR 17 TAHUN 2007 TENTANG TATA KEARSIPAN PADA KANTOR SATUAN BRIGADE MOBILE POLISI DAERAH SUMATERA SELATAN DALAM MENINGKATKAN KINERJA KEANGGOTAAN (STUDI KASUS PADA DETASEMEN A PELOPOR) - M. Sattarudin (UNIVERSITAS INDO GLOBAL MANDIRI, 2019)
The study of the research was the implementation decision of Kapolri No 17, 2007 about the administration of Brigade Mobile unity office, SUMSEL. Increasing the performance of the participant (study case on Detasemen A Pelopor). The aim of the study was knowing and analyzing the case, which related to the implementation the role of Kapolri No 17 ,2007 about the administration of Brigade Mobile Unity. The method was using qualitative approach. The object of the implementation was using communication resource, disposisi, and structure of birokrasi. The process of collecting the data was using by observation, interview and documentation. Analyzing the data was doing by analyze which collected from sistematik data, regular and structured. In this study, there are relation both implementation kapolri no 17, 2007 and filing officer/administration. Limited human resources, infrastructure as a supporting implementation of the administration quality and quantity in a pelopor areaKeywords : implementation, decision Kapolri No 17,2007